PERSEPSI WISATAWAN TERHADAP TAMAN WISATA ALAM CAMPLONG, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Dian Kana Huru; Mamie E. Pelondo'u; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This study aims to determine the tourists' perceptions of the natural tourism park area, and to find out the tourists' perceptions of environmental cleanliness in the Camplong natural tourism park. This research was conducted in November 2019 at the Camplong Nature Tourism Park, Kupang Regency, East Nusa Tenggara Province. Tools and materials used in other research: Cameras, stationery, and questionnaires. The methods used in this study were observation, interview and documentation methods. The results showed that visitors' perceptions of all attractions Camplong natural tourist park is in the